Study on the soil in the mountain-forest area of Kent - Myrzabaev, A.B.; Kuvatbaeva, K.N. (Publ.KarSU, 2018)
The natural cause is the soils of the dry part of the globe, called the soil, under the influence of conditions, and also the value generated by human activity and forming the product of the plant. The only attribute inherent to the soil is fertility. So soil and fertility are twins. The general characteristic of the soil is the loose layer of the earth's surface, changed by the climate conditions of humans, animals and microorganisms, and by humans.Important factors affecting the soil formation process are plant and animal life, climate, soilforming rocks, terrain, geological age, and human production.On the section of the Kent mountain range, on the slope of the southern exposition and on the terrace above the floodplain, four sections were laid. Before describing the soils and sections taken to participate in the mountain range, it is necessary to explain what the mountain mass itself is, and what is the climate on the terrain, and our other aspects influence and are the factors of soil formation. The Kent mountains are a syntrusive granite mountain massif with heights reaching 1500 m, differing in the variety of landscapes and a more humid climate than in the Karkaralinsk mountain massive. The mountain range Kent itself is represented as large, and by small ridges forming a network of rocky ridges separated by gorges, mountain and river valleys.
Кент таулы-орман аймағындағы топыраққа жасалған зерттеу
Исследование почвы в горном лесу в Кенте
Keywords: soil; incision; horizon; mountains; structures; slopes; massive; eluvial; deluvial; Mansell scale